High resolution visualization and exo‐proteomics reveal the physiological role of XlnR and AraR in plant biomass colonization and degradation by Aspergillus niger. (20th October 2017) - Kowalczyk, Joanna E.; Khosravi, Claire; Purvine, Samuel; Dohnalkova, Alice; Chrisler, William B.; Orr, Galya; Robinson, Errol; Zink, Erika; Wiebenga, Ad; Peng, Mao; Battaglia, Evy; Baker, Scott; et al.
Summary: In A. niger, two transcription factors, AraR and XlnR, regulate the production of enzymes involved in degradation of arabinoxylan and catabolism of the releasedl ‐arabinose andd ‐xylose. Deletion of both araR and xlnR in leads to reduced production of (hemi)cellulolytic enzymes and reduced growth on arabinan, arabinogalactan and xylan. In this study, we investigated the colonization and degradation of wheat bran by the A. niger reference strain CBS 137562 and araR / xlnR regulatory mutants using high‐resolution microscopy and exo‐proteomics. We discovered that wheat bran flakes have a 'rough' and 'smooth' surface with substantially different affinity towards fungal hyphae. While colonization of the rough side was possible for all strains, the xlnR mutants struggled to survive on the smooth side of the wheat bran particles after 20 and 40 h post inoculation. Impaired colonization ability of the smooth surface of wheat bran was linked to reduced potential of Δ xlnR to secrete arabinoxylan and cellulose‐degrading enzymes and indicates that XlnR is the major regulator that drives colonization of wheat bran in A. niger .